What It Means to Belong in the Global South: A Coda to Two Special Issues on ‘Wrestling with (Not) Belonging’ - Pasley, Ampersand; Ramirez, Elba; Sturm. Sean (Addleton Academic Publishers, 2024)
Belonging, as this special issue demonstrates, is no simple matter. Indeed, the complexity of the topic demanded a double issue to make space for the many and varied ways in which (not) belonging can make itself felt. Notably, the (not) of (not) belonging in this collection transcends the rationalist reduction of ontology to negative difference, whereby we know what something is through its relation to what it is not. Many contributions acknowledge the injustice of colonial concepts of belonging. While injustice can neither be erased nor resolved once and for all, the works in this double issue demonstrate how attending to these spectres of coloniality offers the possibility of different – and possibly more just – worlds. Several other contributions also explore strategies for knowing and being differently. Some strategies for tending to the wounds of injustice involved more practical enactments. What we sensed when we reread the contributions to write this coda was that the contributions – although differentiated by the contributors’ experiences as people(s) and those of their peoples – had something in common. We saw that they expressed a sense that (not) belonging could be traced in relations of difference, of becoming-with and becoming-otherwise.